2002
DOI: 10.1007/s11910-002-0058-6
|View full text |Cite
|
Sign up to set email alerts
|

Advances in myasthenia gravis

Abstract: Recent advances in the diagnosis and treatment of acquired myasthenia gravis (MG) are reviewed. Increased awareness about the need for more uniform methods of reporting treatment trials for MG has prompted systematic review of the literature and inspired an effort to develop better classifications and disease-specific outcome measures. New antibodies have been discovered in patients with seronegative MG, possibly defining an immunologically distinct form of the disease. A new immunosuppressant, mycophenolate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Using MMF, PSL was tapered from 60 mg to 5 mg in as short a time as 6 months without recurrence of MG in this case, in contrast to the several years usually taken to taper PSL in MG. This demonstrated that MMF can be successfully used for MG associated with cGVHD, as reported for MG unrelated to cGVHD (12).…”
Section: Discussionsupporting
confidence: 58%
“…Using MMF, PSL was tapered from 60 mg to 5 mg in as short a time as 6 months without recurrence of MG in this case, in contrast to the several years usually taken to taper PSL in MG. This demonstrated that MMF can be successfully used for MG associated with cGVHD, as reported for MG unrelated to cGVHD (12).…”
Section: Discussionsupporting
confidence: 58%
“…Myasthenia gravis (MG) is an autoimmune disease characterized by anti‐acetylcholine receptor antibodies and autoimmune lymphocytes . Surgical efficacy of extended thymectomy, which demands an en bloc removal of anterior mediastinal fat tissues , has been widely accepted.…”
Section: Introductionmentioning
confidence: 99%
“…Myasthenia gravis (MG) is an autoimmune disorder of neuromuscular transmission usually mediated by antibodies specific to the human nicotinic acetylcholine receptor (AChR) [1,2]. Autoimmune MG is probably the best understood of the human autoimmune diseases, and our knowledge of its pathogenesis and treatment has increased [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune MG is probably the best understood of the human autoimmune diseases, and our knowledge of its pathogenesis and treatment has increased [2,3]. Treatments include cholinesterase inhibitors, corticosteroids [4,5], and other immunosupressive medications [6 -11].…”
Section: Introductionmentioning
confidence: 99%